Wear of resin composites: Current insights into underlying mechanisms, evaluation methods and influential factors - Akimasa Tsujimoto; Wayne W. Barkmeier; Nicholas G. Fischer; Kie Nojiri; Yuko Nagura; Toshiki Takamizawa; Mark A. Latta; Masashi Miazaki (Elsevier, 2018)
Summary: The application of resin composites in dentistry has become increasingly widespread due to the increased aesthetic demands of patients, improvements in the formulation of resin composites, and the ability of these materials to bond to tooth structures, together with concerns about dental amalgam fillings. As resistance to wear is an important factor in determining the clinical success of resin composite restoratives, this review article defines what constitutes wear and describes the major underlying phenomena involved in this process. Insights are further included on both in vivo and in vitro tests used to determine the wear resistance of resin composite and the relationships between these tests. The discussion focuses on factors that contribute to the wear of resin composite. Finally, future perspectives are included on both clinical and laboratory tests and on the development of resin composite restorations. Keywords: Resin composites, Wear resistance, Wear testing